Building Modules From the Singular Locus - Burke, Jesse; Christensen, Lars Winther; Takahashi, Ryo (Mathematica Scandinavica, 2015)
A finitely generated module over a commutative noetherian ring of finite Krull dimension can be built from the prime ideals in the singular locus by iteration of three procedures: taking extensions, direct summands, and cosyzygies. In 2003 Schoutens gave a bound on the number of iterations required to build any module, and in this note we determine the exact number. This building process yields a stratification of the module category, which we study in detail for local rings that have an isolated singularity.